European large lakes : ecosystem changes and their ecological and socioeconomic impacts - Nõges, Tiina (Springer, 2017)
CLIMATE CHANGE AND ANTHROPOGENIC IMPACTS ON LARGE LAKES ECOSYSTEMS -- FOOD WEB INTERACTIONS AND DYNAMICS IN LARGE LAKES -- MODELING TOOLS IN LARGE LAKES RESEARCH -- WATER POLICY AND SOCIOECONOMIC ASPECTS OF LARGE LAKE MANAGEMENT